2004
DOI: 10.1158/1078-0432.ccr-03-0756
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Lecithin

Abstract: Purpose: Retinoids, which include vitamin A (retinol; ROL) and its derivatives, have been investigated in the treatment of bladder cancer. We have shown that expression of the enzyme lecithin:ROL acyltransferase (LRAT), which converts ROL to retinyl esters, is reduced in several human cancers. Here we evaluated expression of LRAT protein and mRNA in normal and malignant bladder tissue specimens from human patients. We also examined the effect of retinoids on LRAT expression in bladder cancer cell lines.Experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 41 publications
(46 reference statements)
1
26
1
Order By: Relevance
“…Lecithin retinol acyltransferase (LRAT), an enzyme responsible for the esterification of retinol to retinyl ester (Ruiz et al, 1999), was suggested to be the founder of the eukaryotic members of this superfamily (Anantharaman and Aravind, 2003). Similar to H-REV107-like proteins, LRAT expression is reduced in several human tumors and in corresponding cell lines (Andreola et al, 2000;Boorjian et al, 2004;Guo et al, 2000;Guo et al, 2001;Guo et al, 2002;Guo and Gudas, 1998;Jurukovski and Simon, 1999;Simmons et al, 2002;Zhan et al, 2003). In contrast to the H-REV107 proteins and most of the prokaryotic related proteins, LRAT has a defined biochemical function and the active motifs within the protein have been characterized (Mondal et al, 2000;Mondal et al, 2001;Xue and Rando, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Lecithin retinol acyltransferase (LRAT), an enzyme responsible for the esterification of retinol to retinyl ester (Ruiz et al, 1999), was suggested to be the founder of the eukaryotic members of this superfamily (Anantharaman and Aravind, 2003). Similar to H-REV107-like proteins, LRAT expression is reduced in several human tumors and in corresponding cell lines (Andreola et al, 2000;Boorjian et al, 2004;Guo et al, 2000;Guo et al, 2001;Guo et al, 2002;Guo and Gudas, 1998;Jurukovski and Simon, 1999;Simmons et al, 2002;Zhan et al, 2003). In contrast to the H-REV107 proteins and most of the prokaryotic related proteins, LRAT has a defined biochemical function and the active motifs within the protein have been characterized (Mondal et al, 2000;Mondal et al, 2001;Xue and Rando, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Reduced expression of LRAT has been found in different types of cancer, for example bladder, kidney, prostate, breast and oral cavity (13)(14)(15)(16). In bladder cancer, LRAT protein expression correlated with tumor stage of the primary; in most invasive tumors, it was absent (14). This matches the finding that LRAT might have tumor-suppressor properties (17).…”
Section: Discussionmentioning
confidence: 99%
“…The esterification of retinoids to retinyl esters is an important mechanism for maintaining tissue retinoids in a form that is easily stored and readily mobilized for additional metabolic needs (39). Recent reports have indicated there is a significant reduction in lecithin retinol acyltransferase expression in cancer compared with normal tissues, as well as an inverse correlation of this expression with increasing tumor stage (40). Therefore, restoration of lecithin retinol acyltransferase expression may be a reasonable strategy for cancer therapy.…”
Section: Discussionmentioning
confidence: 99%